Violência e homicídios relacionados ao tráfico de drogas, em Uberlândia - MG - Britto, Cristiano Quirino de (2017)
Uberlandia is a city in the Southeastern of Brazil, in the Triangulo Mineiro region, at the intersection of the geographical coordinates 18°55'23 '' South Latitude and 48°17'19 '' West Longitude. It is located to the west of the state capital, Belo Horizonte and the distance between them is about 556 kilometers. It is surrounded by the municipalities of Araguari, Indianopolis, Monte Alegre de Minas, Prata, Tupaciguara, Uberaba and Verissimo. The main objective of this research is to understand homicides related to drug trafficking and propose strategies to prevent and reduce violence in Uberlandia. For these reasons, municipalities of the following specific objectives were established: to understand homicide and its motivations, as well as its legal norms throughout history; to understand the world of drugs and traffickers on duty at major events; to identify violence and homicides related to drug trafficking in Uberlandia; to propose a strategy to prevent homicides related to drug trafficking in Uberlandia, based on the Project for Disarmament and Operation Cease Fire in the city of Boston (Massachusetts / USA). The methodological path was developed considering the following steps: survey and analysis of bibliography available for theoretical- methodological orientation regarding the occurrence of homicides caused by drug trafficking in Uberlandia and in other countries; the world of drugs, drug users, traffickers on duty and the main types of synthetic and non-synthetic drugs. The data from this study were collected as part of a larger study on the problem of homicide caused by drug trafficking in the city of Uberlandia in the years2010 to 2014. Homicide data in Uberlandia were collected from 679 REDS Social Security Event), semi structured, formal or by guidelines, with spatial profile records of homicides: place of occurrence, day, month and year, weapon used, age range of perpetrators and people directly involved. Other objects of study were the rave parties, concerts and nightclubs using the observation method, informal conversations, reports, and research participation mostly in the city of Uberlandia. A total of 679 completed homicides were investigated, in a total of approximately 528 (78%) occurrences of homicides caused by drug trafficking. The 151 remaining cases (22%), represented the crimes of extortion through kidnapping, robbery and taking against will. These data reveal a negative growth of homicide rates. As most of the cases of homicides registered in Uberlandia are directly related to drug trafficking, especially by young menand women, the relevance of a short-term decision by the city's public authorities is clear. This assessment was proposed in this work through a plan for the prevention and minimization of homicides for the city of Uberlandia referenced in the Boston Project.